Development of proficiency-based knot-tying and suturing curriculum for otolaryngology residents: A pilot study. Issue 2 (April 2020) - Sato, Eriko; Mitani, Sohei; Nishio, Naoki; Kitani, Takashi; Sanada, Tomoyoshi; Ugumori, Toru; Christopher Holsinger, F.; Baik, Fred M.; Hato, Naohito
Abstract: Objective: Basic surgical skills such as knot-tying and suturing are important for all otolaryngologists, regardless of subspecialty. The present study was undertaken in order to assess basic surgical techniques such as knot-tying and suturing required for novice otolaryngology residents with taking the variety of subspecialties into consideration, and evaluate the impact of a proficiency-based training curriculum based on these techniques. Methods: A prospective study was performed for developing of proficiency-based knot-tying and suturing curriculum for otolaryngology residents in the third post-graduate year (PGY-3). The proficiency-based training curriculum was developed based on the tasks selected by RAND/UCLA method with expert panel, which is an iterative and anonymous survey used to establish consensus among participants. Expert panelists were selected from various divisions to reflect variety of their subspecialties. PGY-3 residents trained with the developed curriculum that included proctored pre-test, self-training to proficiency, and proctored post-test. Visual analogue scale (VAS) of trainees' overall competence in the operating room was self-assessed by each resident, before and after completing the training curriculum. Results: Nine PGY-3 residents were enrolled as trainees. Eleven experts chosen as panelists had various subspecialty, including 2 from otology, 2 from rhinology, 2 from laryngology, 2 from head and neck surgery, and 3 from general otolaryngology. Seven tasks were selected from RAND/UCLA method and used to develop the curriculum. Trainee scores at pre-test were significantly lower than expert scores for all 7 tasks ( p < 0.01) and each coefficient of variation of trainee score was larger than that of expert score ( p < 0.05), supporting construct validity. The mean of composite scores between pre-test and post-test had statistical significance (68.6 ± 11.6 vs 95.9 ± 3.6, p < 0.01), documenting substantial improvement after training. Self-assessment VAS was also improved pre- to post-training (1.2 ± 0.9 vs 4.5 ± 1.4, p < 0.01). A follow-up questionnaire showed that trainees felt the educational curriculum to be beneficial. Conclusion: In the present study, seven basic technical skills were selected using the RAND/UCLA method and used to create a proficiency-based training curriculum. Our results indicate that this curriculum significantly improves proficiency of basic surgical skills of junior otolaryngology residents.